Analysis of marketing strategy in increasing the number of tourist visits at the Le Hu Garden tourist attraction, Deli Serdang regency - Ririn Chairani Sinaga; Edi Winata (SEAN Institute, 2024)
The purpose of this research is to know how the marketing strategies increase the number of tourist visits to the tourist attraction The Le Hu Garden, Deli Serdang Regency. Data analysis used qualitative descriptive methods and conducted interviews and data collection which was carried out by searching for information based on documents related to research and comparing data from observations made at The Le Hu Garden. From the results of research using Swot Analysis at The Le Hu Garden tourist attraction, the first is the strength of having a unique garden that is specially cared for and natural fertilizer which makes plants grow abundantly which other tourist attractions do not have, weakness Lack of Promotional activities carried out include the absence of cooperation with travel, opportunities Large land, can be used to add new attractions suitable for agrotourism such as growing hydroponic vegetables, raising livestock and fish cultivation, threats Competitor tourist attractions of the same type create more varied places.